East of Malta, west of Suez : the admiralty account of the naval war in the eastern mediterranean, September 1939 to March 1941 : prepared for the Admiralty (London : His Majesty's Stationery Office, 1943)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Wereldoorlog 2; Middellandse Zeegebied